Methodological Approach to the Reengineering of Logistics Business Processes in the Transport Chains with the Implementation of Smart Contracts - T. G. Shul’zhenko (Управленческие науки)
The article analysis the methodological justification of the digital transformation of logistics processes in transport chains formed by transport and logistics companies at the national and transnational levels, which own their own infrastructure, when switching to the technology of smart contracts. The research methodology is based on the provisions of the theory of logistics and supply chain management, the theory of process management and the design and technological concept of organizational culture formation. Based on the results of the established principles of transition to smart contract technology, digital transformation of processes, a logical and time structure of the methodology of engineering/reengineering of logistics business processes in transport chains was formed during the transition to smart contract technology, which provides the most complete coverage of methodological problems solved in the process of reengineering, their logical focus, as well as correlation with the time frame. The study presents a methodological tool and results of semantic modeling of logistics processes in transport chains that form the necessary basis for further algorithmization of procedures for fulfilling the contractual conditions of a smart contract. Based on the systematization of approaches to establishing the essential characteristics of smart contracts, their models are established, as well as the necessary conditions for the successful implementation of various smart contract models and possible transition scenarios are identified. The materials of the article are largely the result of close interaction with JSC “Russian Railways” in the course of preparing a methodological justification for the transition to the technology of smart contracts in transport chains, the logical processes in which are implemented using the railway infrastructure of JSC “Russian Railways”.